Overview of Internet of vehicles for 5G - Liang-min WANG; Xiao-long LIU; Chun-xiao LI; Jing YANG; Wei-dong YANG (网络与信息安全学报)
The functions and characteristics of current IOV(Internet of vehicles) Internet of vehicles were analyzed.Moreover,combined with 5G communication technology,the architecture of IOV for 5G was proposed to imple-ment access and integration of multi-network.Different from the IEEE 802.11p based architecture of VANET,de-vice-to-device (D2D) technology was introduced to achieve flexible terminals communication of IOV.In comparing with VANET based on IEEE 802.11p in terms of key technology parameters,the IOV for 5G possesses the better characteristics in terms of low latency and efficient spectrum utilization,and also need to face new interference management and security challenges.At the end,the application and development trends of IOV for 5G in the busi-ness and the specific environment were prospected.